The Making of the Modern Iranian Women: Gender, State Policy, and Popular Culture, 1865-1946 by Camron Michael Amin (Gainesville: University Press of Florida. 2002. 320 pages.) (American Journal of Islam and Society, 2004)
The book, a detailed historical examination of an important era of contemporaryIran’s history, documents a variety of late-nineteenth-centuryviews on “the women’s question.” Amin’s attempt to review its historicalbackground is an excellent gender-perspective analysis of the politicalatmosphere existing before Iran’s constitutional revolution of 1906-08.The intellectual debate ranged enormously during this period. For example,the atheist Akhundzadeh blamed Islamic and Turkmen rule (CentralAsians tribal rulers who had invaded Iran throughout Iranian history) fortheir situation. Meanwhile, the Babist Kermani, who called Iranian women“the living dead,” saw their enslavement as the result of the corrupted Arabculture transmitted through Islam. The example of such “progressives” asTaghizadeh, who followed western ideas and used the most racist and sexistarguments against women’s equality, presents an interesting aspect ofwesternization, which is brought up in the book.Alongside these different views, Amin documents a different andequally valuable late-nineteenth-century response that sought equality forwomen within Islam. This trend, similar to that of Qasim Amin of Egypt,includes as its most notable example Jamal al-Din Asadabdi, who supporteda modern interpretation of Islam that included gender equality.Mirza Malkam Khan, publisher of Ghanon (The Law), a newspaper printedin exile, was the first person to transform the “women’s question” froman elite discussion to a matter of Iranian public discourse through the press.He argued that women must be treated as human beings with the same dignitythat was accorded to men.Amin delineates two responses to the women’s question: a misogynistview that is best illustrated by Ta’dib al Nesvan (Disciplining Women),published during 1882-89, and a reaction to it written by Bibi KhanomAstarabadi, authoress of Ma’ayb al Rejal (The Vice of Men). Astarabadi (insome ways she can be called the first Muslim feminist) condemned suchmisogynous practices as infidelity and temporary marriage, as well as thedrinking, gambling, and pedophilia practiced by some men.The most interesting part of the book is the author’s discussion ofReza Shah and his break with the Qajar dynasty. Reza Shah imposed his ...